Experimental systems : future knowledge in artistic research - Schwab, Michael (Leuven : Leuven University Press, 2013)
- Introduction / Michael Schwab##- A Theory of Experimentation in Art? Reading Kubler’s History of Art after Rheinberger’s Experimental Systems / Stefanie Stallschus##- Electrical Images: Snapshots of an Exploration / Hannes Rickli##- Material Experiments: “Phenomeno-Technology” in the Art of the New Materialists / Susanne Witzgall##- Whatever Remains, However Improbable: British Experimental Music and Experimental Systems / Virginia Anderson##- Of Arnold Schoenberg’s Klavierstück op. 33a, “a Game of Chess,” and the Emergence of New Epistemic Things / Darla M. Crispin##- Research Organs as Experimental Systems: Constructivist Notions of Experimentation in Artistic Research / Peter Peters##- A Laboratory View of Art / Gabriele Gramelsberger##- Artistic Practices and Epistemic Things / Henk Borgdorff##- Artistic Experiments as Research / Elke Bippus##- Toward a Practice of Novel Epistemic Artefacts / Stephen A. R. Scrivener##- Epistemic Complexity and Experimental Systems in Music Performance / Paulo de Assis##- Criticism and Experimental Systems / Paolo Giudici##- Epistemic Events / Neal White##- Forming and Being Informed / Hans-Jörg Rheinberger in conversation with Michael Schwab
boek